Identification of the Francisella novicida FTN_0096 as a factor involved in intracellular replication and host response - Dhandy Koesoemo Wardhana; Takashi Shimizu; Kenta Watanabe; Akihiko Uda; Masahisa Watarai (PLoS ONE, 2025)
Francisella tularensis is the causative agent of the zoonotic disease tularemia. We investigated a pathogenic factor of F. tularensis subsp. novicida (F. novicida). Accordingly, we established a novel infection model using HeLa cells. F. novicida usually infects macrophage lineage cells and less frequently epithelial cells. We successfully infected HeLa cells expressing the Fc receptor (HeLa–FcγRII cells) using F. novicida supplemented with mouse serum containing F. novicida antibodies. A total of 2,232 transposon mutants of F. novicida were screened to determine the relatively fewer cytotoxic strains of the HeLa–FcγRII cells, and 13 strains were thus isolated. Sequencing analysis of transposon insertion sites identified 13 genes, including FTN_0096. We focused on FTN_0096. Although the F. novicida wild-type strain proliferated in HeLa–FcγRII and THP-1 cells, the number of intracellular FTN_0096 mutant decreased. FTN_0096 mutant cannot escape from phagolysosomes in the initial phases of infection. Moreover, FTN_0096 mutant was detected in the mitochondria and Golgi complex. These findings indicate the importance of FTN_0096 of F. novicida for intracellular replication in the cells.